Data from: De novo assembly of two Swedish genomes reveals missing segments from the human GRCh38 reference and improves variant calling of population-scale sequencing data - Adam Ameur; Ulf Gyllensten (Uppsala University, 2018)
De novo assembly of two individuals from the SweGen dataset
Keywords: Nucleotide sequence data; Medical and Health Sciences; Medicin och hälsovetenskap